Community-based participatory research - Hacker, Karen (SAGE, 2013)
"Community-Based Participatory Research by Dr. Karen Hacker presents a practical approach to CBPR by describing how an individual researcher might understand and then actually conduct CBPR research. This how-to book provides a concise overview of CBPR theoretical underpinnings, methods considerations, and ethical issues in an accessible format interspersed with real-life case examples that can enhance the study of research methods in multiple disciplines."--From cover.